PROBLEMS OF MARRIAGE GUARDIANS IN SUPREME COURT DECISIONS: GENDER PERSPECTIVE ANALYSIS - Muhammad Idris Nasution; Mustapa Khamal Rokan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Family law in some countries regulates guardianship in marriage as a pillar that applies absolutely, that a marriage is considered invalid and can be canceled if it is carried out without a guardian or with an unauthorized guardian. A handful of women activists consider guardianship over women to obstruct the realization of their rights and discriminate against women, including male guardianship over women in this marriage. Long before the issue of guardianship heated up again, the Supreme Court had actually faced cases of parents trying to cancel their child's marriage because it was done with an unauthorized guardian. The court of first instance and appellate level had annulled the marriage, but the Supreme Court at the cassation level actually viewed the marriage as legal according to Islamic law. The author in this article will analyze this decision using the method of explanative analysis and describe it with thematic content. Analysis of this decision leads us to discuss the problem of women marrying themselves off, women representing their marriages and women being guardians of marriage from a gender perspective. This finding shows the dynamics of guardianship law over women in marriage. Based on the principle of al-musāwah, the basic principle in marital guardianship is that men and women are equal; may not distinguish legal provisions between men and women based solely on their gender, except based on benefit.